Geo-Informatics in Resource Management - Mesas Carrascosa, Francisco Javier (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The management of natural resources can be approached using different data sources and techniques, from images registered by sensors of onboard satellites to UAV platforms, using remote sensing techniques and geographic information systems, among others. The variability of problems and projects to be analyzed, studied, and solved is very wide. This book presents a collection of different experiences, ranging from the location of areas of interest to the simulation of future scenarios of a territory at local and regional scales, considering spatial resolutions ranging from centimeters to hundreds of meters. The common objective of all the works compiled in this book is to support decision-making in environmental management.